2011
DOI: 10.1159/000322845
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Ca<sup>2+</sup> Regulation of CD4<sup>+</sup>CD25<sup>+</sup> Regulatory T Cells from Pediatric Asthma

Abstract: Background: CD4+CD25+ regulatory T (Treg) cells can control the allergic response to allergen, airway eosinophilia and airway hypersensitivity. We speculated that chronic inflammation persisting in asthma airways is dependent on abnormalities of these Treg cells. There are differences in the pathology of asthma in adults and children, and the airways of pediatric asthma are considered to be more naive than those of adults. Therefore, we analyzed the functionality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 60 publications
1
18
2
Order By: Relevance
“…In adult humans, the regulatory function of Treg cells was reduced in symptomatic hay fever subjects during the pollen season but not in asymptomatic status from the same population outside of the pollen season (Ling et al, 2004). Ca 2+ signaling is very important for lymphocyte functions and our own data have indicated that impaired Ca 2+ regulation within CD4 + CD25 + CD45RO + Treg cells correlated with child asthma symptoms (Yamamoto et al, 2011). We showed that anergy, one of the defining human Treg cell features, is dependent on intra-cellular calcium.…”
Section: The Role Of Treg Cells In Childhood Asthmamentioning
confidence: 75%
See 2 more Smart Citations
“…In adult humans, the regulatory function of Treg cells was reduced in symptomatic hay fever subjects during the pollen season but not in asymptomatic status from the same population outside of the pollen season (Ling et al, 2004). Ca 2+ signaling is very important for lymphocyte functions and our own data have indicated that impaired Ca 2+ regulation within CD4 + CD25 + CD45RO + Treg cells correlated with child asthma symptoms (Yamamoto et al, 2011). We showed that anergy, one of the defining human Treg cell features, is dependent on intra-cellular calcium.…”
Section: The Role Of Treg Cells In Childhood Asthmamentioning
confidence: 75%
“…In contrast to effector T cells, CD4 + CD25 + Treg cells produce less IL-2, proliferate poorly, and exhibit a low level of Ca 2+ influx in response to TCR stimulation (Gavin et al, 2002;Yamamoto et al, 2011). The decline of IL-2 transcription in Treg cells is mainly attributed to the master regulator FOXP3, which is able to inhibit the function of NFAT by competing with its binding to AP-1 (Wu et al, 2006).…”
Section: Different Mechanisms Of Determining Anergic Status In Treg Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The results may reveal that highly exposed, allergic and asthmatic children could be resistant to usual allergen-induced regulatory mechanisms due to undefined molecular impairments(Yamamoto, Negoro et al 2011), or the contribution of other genes or CpG sites within the same genes, or even other epigenetic pathways like histone acetylation or hydroxymethylation(Planell-Saguer, Lovinsky-Desir et al 2014). However, the results also do not support the paradigm that decreased FOXP3 methylation is part of the causal pathway leading to changes in mouse IgE, at least according to this timeline for a clinical allergic response.…”
Section: Resultsmentioning
confidence: 99%
“…These possibilities are of particular interest in light of reports that environmental exposure to airborne bacterial lipopolysaccharide in childhood may be protective against Th2-mediated sensitization to inhalant allergens. 39,278,279 It is pertinent to note that these exposures have also been observed to enhance postnatal maturation of IFN-γ-producing capacity, 280 a lack of which has been identified as a risk factor for allergy by our group and others. 271 A range of immune-associated mechanisms may contribute to these effects including modulation of TLR function initially in decidual tissue at the fetomaternal interface 272,273 and subsequently within the developing innate immune system of the offspring.…”
Section: Granulocyte Populationsmentioning
confidence: 90%